The Myth of Self-Knowledge in Genesis 1-2: The Fascination of the Encounter - Esparza, Gustavo (Brill, 2021)
My purpose in this paper is to analyze the encounter between Adam and Eve as it is described in Genesis 1–2. Here I consider the myth as a valid source of self-knowledge, inasmuch as through its narration it is possible to experience the moment of fascination in which “man” realizes that “woman” is “bones of his bones and flesh of his flesh.” I will emphazise that this expression is developed through a phenomenological process which implies, in turn, a pedagogical path to form in man the capacity to understand the woman as the culminating point of creation, and that, being “like” me means being different from me.
Fascination of the Encounter